KONSEP PENYELESAIAN ISTRI NUSYŪZ TELAAH KITAB UQUD AL-LUJAIN - Ahmad Zuhairus Zaman, Hana Nur Nafi’ah (Mabahits : Jurnal Hukum Keluarga Islam, 2022)
Ulama 'calls Nusyūz as a wife's deviation to her husband. This research will explain the concept of Nusyūz from Shaykh Nawawi Albantani in the book of Uqud Al-Lujain. By using a qualitative approach to the library research which with this research will produce how the opinion of Shaykh Nawawi about Nusyūz and how the relevance of Shaykh Nawawi's opinion with the pesantren community. Shaykh Nawawi in explaining Nusyūz was only charged to the wife, this was because the husband had given dowry and a living in marriage, therefore the husband had the right to get the wife's obedience. While the relevance of the Nusyūz problem with the context of the pesantren community is now irrelevant because the pesantren community is not specializing in Nusyūz to the wife.